On Electrodeless Induction Lamps - Bhattacharya, Sourin; Majumder, Nirab (International Journal of Computer Sciences and Engineering, 2025)
This paper reviews the current technology & trends of electrodeless lamps, videlicet, fluorescent induction lamps & sulphur lamps. Induction lamps utilize the principle of electromagnetic induction & visible light is generated by phosphor coating in case of fluorescent lamps and by sulphur molecules in case of sulphur lamps. The methodologies of light generation, lighting characteristics, application areas, advantages & disadvantages in their utilization & the future scope of improvement are hereby duly expounded & analysed.